2005
DOI: 10.1007/s10620-005-2854-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Prognosis in Gallbladder Carcinoma by Mucin and p53 Immunohistochemistry

Abstract: Mucin core proteins are known to be present in various organs and are specifically expressed with carcinogenesis and closely associated with the prognoses of various malignant tumors in the digestive tract such as colorectal cancer. The present study evaluated correlations between mucin and p53 expression and prognosis of gallbladder cancer using surgically resected tissue specimens from 26 patients with gallbladder carcinoma surgically treated at our hospital. Immunohistochemical staining was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 15 publications
3
22
1
Order By: Relevance
“…These observations support the theory that MUC1 expression could be particularly prevalent in gallbladder carcinoma, and could contribute to the progression of gallbladder carcinomas. Regarding the prognostic value of MUC1 expression in gallbladder carcinoma, several studies described an association with a poor outcome in univariate analysis [34,35], but this study showed no relation between MUC1 expression and the outcome of patients with gallbladder carcinoma. This difference might be explained by various glycoforms of the MUC1 antigen, including underglycosylated, sialylated, and fully glycosylated forms [6], and these discrepancies in expression rates.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…These observations support the theory that MUC1 expression could be particularly prevalent in gallbladder carcinoma, and could contribute to the progression of gallbladder carcinomas. Regarding the prognostic value of MUC1 expression in gallbladder carcinoma, several studies described an association with a poor outcome in univariate analysis [34,35], but this study showed no relation between MUC1 expression and the outcome of patients with gallbladder carcinoma. This difference might be explained by various glycoforms of the MUC1 antigen, including underglycosylated, sialylated, and fully glycosylated forms [6], and these discrepancies in expression rates.…”
Section: Discussioncontrasting
confidence: 64%
“…These results suggest that MUC2 expression is related to noninvasive proliferation of the tumor, resulting in a favorable outcome. But MUC2 expression has not been related to clinical outcome in gallbladder carcinoma [34,35]. This study also found that although MUC2 expression appeared linked to better survival, this was not statistically significant.…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, other investigations reported a role of p53 gene mutation in the transition from premalignancy to malignancy (Ajiki et al 1996;Moreno et al 2005) and a correlation between p53 expression in CG and poor survival (Takagawa et al 2005). An important regulator of chromatin, involved in silencing tumor suppressor genes, is the histone deacetylase (HDAC) system.…”
Section: Oncogene and Tumor Suppressor Gene Expression And Factors Inmentioning
confidence: 94%
“…Rate and pattern of MUC1 protein expression suggest that MUC1 would be a marker of malignant transformation of invasion of gallbladder cancer [365,366]. Prognostic value of mucin (MUC1 and MUC2) in gallbladder carcinoma along with other tumor growth factors (like p53 was carried out but Mucin expression was found to be independent of various tumor growth factors and clearly reflected the prognosis of gallbladder cancer [367].…”
Section: Gallbladder Gallbladder Inflammation and Stone Formationmentioning
confidence: 98%